2022
DOI: 10.21203/rs.3.rs-1716096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pilot randomized controlled trial of supervised, at-home, self-administered transcutaneous auricular vagus nerve stimulation (taVNS) to manage long COVID symptoms

Abstract: Background Although the coronavirus disease 19 (COVID-19) pandemic has now impacted the world for over two years, the persistent secondary neuropsychiatric effects are still not fully understood. These “long COVID” symptoms, also referred to as post-acute sequelae of SARS-CoV-2 infection (PASC), can persist for months after infection without any effective treatments. Long COVID involves a complex heterogenous symptomology and can lead to disability and limit work. Long COVID symptoms may be due to sustained i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…A recent double-blind, sham-controlled pilot study assessed the impact of a four-week at-home treatment with self-administered electrical transcutaneous auricular vagus nerve stimulation (Soterix Medical, Inc. (Woodbridge, New Jersey, United States); 25 Hz, 500 μs pulse width, tonically on for 1 h, twice daily, 6 days per week, twice individual perceptual threshold intensity) to manage long-COVID symptoms. This VNS treatment was not only safe and highly compliance-rated, but also revealed interesting trends in reducing mental fatigue scores [ 115 ]. Therefore, transcutaneous auricular VNS appears to be a promising therapeutic option to manage chronic fatigue syndrome.…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…A recent double-blind, sham-controlled pilot study assessed the impact of a four-week at-home treatment with self-administered electrical transcutaneous auricular vagus nerve stimulation (Soterix Medical, Inc. (Woodbridge, New Jersey, United States); 25 Hz, 500 μs pulse width, tonically on for 1 h, twice daily, 6 days per week, twice individual perceptual threshold intensity) to manage long-COVID symptoms. This VNS treatment was not only safe and highly compliance-rated, but also revealed interesting trends in reducing mental fatigue scores [ 115 ]. Therefore, transcutaneous auricular VNS appears to be a promising therapeutic option to manage chronic fatigue syndrome.…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…1 Early evidence from similar devices suggests that noninvasive neurostimulation could help alleviate some symptoms related to the long-term effects of COVID-19. 13,14 Who Might Benefit?…”
Section: How It Workmentioning
confidence: 99%
“…A preprint paper from the US reported results from a study where people with at least 1 symptom associated with post-COVID-19 condition self-administered noninvasive vagus nerve stimulation (using a device similar to the Dolphin Neurostim) at home. 13 In total, 24 people were assigned to either a sham or active treatment group for a 4-week study period, with each group having 12 participants. The study reported that the participants confidently administered the therapy without assistance after 3 days of guided virtual sessions.…”
Section: Emerging Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies with a small sample sizes have shown that patients suffering from PCC had a range of functional and/or structural alterations in the vagus nerve, supporting the existence of a correlation between PCC and autonomic imbalance in which vagal nerve activity is decreased [20,21]. The activity of the vagus nerve can be indexed by the measurement of heart-rate-variability (HRV).…”
Section: Introductionmentioning
confidence: 99%